HMGB1 Is Involved in Chronic Rejection of Cardiac Allograft via Promoting Inflammatory‐Like mDCs. Issue 8 (1st July 2014) - Zou, H.; Yang, Y.; Gao, M.; Zhang, B.; Ming, B.; Sun, Y.; Chen, H.; Tang, X.; Chen, Z.; Xiong, P.; Xu, Y.; Fang, M.; et al.
<x xml:space="preserve">Abstract</x> Chronic rejection that leads to diffuse narrowing and occlusion of graft vessels is the most important cause of morbidity and mortality following cardiac transplantation. The role and underlying mechanism of high‐mobility group box 1 (HMGB1), as an established inflammatory mediator in acute rejection, remains poorly understood in chronic rejection. Here, we assessed the effects and mechanisms of HMGB1 on the chronic rejection using single MHC Class II‐mismatched mouse cardiac transplantation model. It was found that HMGB1 was increased accompanying with the development of chronic rejection, while blockade of HMGB1 with specific neutralizing mAb substantially ameliorated chronic rejection‐mediated vasculopathy and fibrosis of allograft, as well as markedly decreased T cell infiltration and production of IL‐17A and interferon‐gamma in allograft and recipient's spleen. Further, anti‐HMGB1 antibody treatment significantly declined the number and frequency of mature dendritic cells (DCs) in allograft and recipient's spleen, especially CD11b+Ly6Chigh matured DCs that share the phenotypes with inflammatory‐DCs. These findings indicate that HMGB1 contributes to chronic rejection, and HMGB1 blockade may be a novel mean to disrupt the proinflammatory loop after heart transplantation.